(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
ABSTRACT Maternal mortality remains a significant public health issue, particularly in rural regions of developing countries. Early pregnancy (pregnancy among adolescents and young women) is a major contributor to maternal deaths, resulting in profound impacts on community health and well-being. This study focuses on Reckjoani Rural Hospital in Rajarhat Block, West Bengal, to explore the prevalence, causes, and effects of maternal mortality due to early pregnancy. The objective of the study focused on the below To determine the incidence of maternal mortality among early pregnancies in Reckjoani Rural Hospital. To identify the primary causes contributing to maternal deaths in young mothers. To analyse the impact of these deaths on community healthcare and overall community health. A mixed-method approach was employed, combining quantitative data from hospital records (2023-2024) with qualitative information and data through personal interviews. Quantitative data were analysed to identify trends and common causes of maternal deaths, while qualitative data provided insights into the socio-economic and cultural factors that are influencing early pregnancies and maternal health results and outcomes. The study found that maternal mortality among early pregnancies in Reckjoani Rural Hospital is alarmingly high. Key factors contributing to these deaths include lack of access to prenatal care, inadequate healthcare infrastructure, socio-economic barriers, and cultural practices. The qualitative analysis revealed that early marriage, limited education, and poverty are significant underlying contributors to early pregnancies. The impact on community healthcare is profound, with increased healthcare costs, emotional and psychological stress on families, and loss of productive workforce being notable consequences. Maternal mortality due to early pregnancy in Reckjoani Rural Hospital presents a critical public health challenge. To conduct the study on this issues it requires a multi-focused approach, including implementation of minimum marriage age laws at panchayat ,an elective village council in India level, improving healthcare infrastructure, enhancing access to education, and implementing community-based awareness to delay the age of first pregnancy. Strengthening healthcare policies like Janani Suraksha Yojana (JSY), Weekly Iron and Folic Acid Supplement (WIFS) programmes under National Health Mission (NHM) by continuous effort by health workers, teachers and block official, increasing community awareness are essential steps towards reducing maternal mortality and improving community health outcomes in Rajarhat Block, West Bengal.